Oxford EAP / A course in English for Academic Purposes Upper - Intermediate B1+ - Teacher's Handbook - Chazal Edward; Rogers Louis (Oxford University Press, 2013)
Upper- Intermediate/ B1+ - Intergraded skills & language - Authentic Academic texts - Incudes CD-ROM. Course Introduction, Teaching Notes and Answers and Suggestions for Extension Tasks and Further Practice, Knowledge, Organization, Motivation, Nature, Power, Growth, Networks, Innovation, Consumption, Crime, Energy, Progress, Audio CD Track Listing Page.